Connectivity of pacemaker neurons in the neonatal rat superficial dorsal horn. Issue 7 (17th February 2015) - Li, Jie; Kritzer, Elizabeth; Ford, Neil C.; Arbabi, Shahriar; Baccei, Mark L.
ABSTRACT Pacemaker neurons with an intrinsic ability to generate rhythmic burst‐firing have been characterized in lamina I of the neonatal spinal cord, where they are innervated by high‐threshold sensory afferents. However, little is known about the output of these pacemakers, as the neuronal populations that are targeted by pacemaker axons have yet to be identified. The present study combines patch‐clamp recordings in the intact neonatal rat spinal cord with tract‐tracing to demonstrate that lamina I pacemaker neurons contact multiple spinal motor pathways during early life. Retrograde labeling of premotor interneurons with the trans‐synaptic pseudorabies virus PRV‐152 revealed the presence of burst‐firing in PRV‐infected lamina I neurons, thereby confirming that pacemakers are synaptically coupled to motor networks in the spinal ventral horn. Notably, two classes of pacemakers could be distinguished in lamina I based on cell size and the pattern of their axonal projections. Whereas small pacemaker neurons possessed ramified axons that contacted ipsilateral motor circuits, large pacemaker neurons had unbranched axons that crossed the midline and ascended rostrally in the contralateral white matter. Recordings from identified spino‐parabrachial and spino‐periaqueductal gray neurons indicated the presence of pacemaker activity within neonatal lamina I projection neurons. Overall, these results show that lamina I pacemakers are positioned to regulate both the level of activity in developing motor circuits and the ascending flow of nociceptive information to the brain, thus highlighting a potential role for pacemaker activity in the maturation of pain and sensorimotor networks in the central nervous system. J. Comp. Neurol. 523:1038–1053, 2015. © 2015 Wiley Periodicals, Inc.